A novel splicing variant in GALNS in mucopolysaccharidosis IVA and the necessity of re‐evaluating primer sequences. (24th August 2022) - Kim, Sang‐Mi; Noh, Eu Seon; Park, Jong‐Ho; Park, Hyung‐Doo; Lee, Soo‐Youn; Jang, Ja‐Hyun; Cho, Sung Yoon
Abstract : Abstract: Mucopolysaccharidosis type IVA (MPS IVA; Morquio syndrome type A) is an autosomal recessive disorder caused by defects in the lysosomal hydrolase N‐acetylgalactosamine‐6‐sulfatase ( GALNS ) gene, leading to progressive systemic skeletal dysplasia. Early diagnosis and early intervention with enzyme replacement therapy are crucial for improving outcomes in these patients. However, a relatively high number of patients are genetically undiagnosed due to high allelic heterogeneity and the absence of robust functional evidence for most variants of the GALNS gene. Herein, we report a novel intronic variant identified with RNA analysis and an allele dropout (ADO) event caused by a common benign variant in the primer‐binding site in a Korean boy with MPS IVA. A 28‐month‐old boy presented with pectus carinatum, kyphoscoliosis, and joint hypermobility with multiple skeletal dysplasia involving the vertebrae and hip joint. Total urinary glycosaminoglycans were elevated with a predominant keratan sulfate fraction, and GALNS (EC 3.1.6.4) activity was significantly decreased in leukocytes. Sanger sequencing was performed; however, only one heterozygous intronic variant with uncertain clinical significance, c.566+3A > T (p.(?)), was identified. As the patient exhibited clinical and biochemical features of MPS IVA, we conducted whole genome sequencing (WGS) of the patient and his family to clarify the molecular diagnosis. WGS revealed a compound heterozygous genotype, c.1019G > A (p.(Gly340Asp)) and c.566+3A > T (p.(?)), in the GALNS gene. On mRNA sequencing, c.566+3A > T, was confirmed to cause exon 5 skipping and a premature stop codon. With subsequent investigation, we discovered that the variant, c.1019G > A, was undetected on initial sequencing because of ADO due to a common benign variant (rs3859024:G > C) at the primer annealing location. We present a novel intronic variant with a splicing defect in the GALNS gene and suggest that clinicians review primer sequences in cases not diagnosed on Sanger sequencing before progressing to diagnostic steps such as WGS.